Verification of Design Equations for Ductile Failure Mode in Bolted Connections of Local Hardwoods. - Abdul Razak, Abdul Karim; Norazzlina, M. Sa'don; Muhammad Hafiz, Zainal Abidin; Siti Noor Atikah, Ihwan (Universiti Malaysia Sarawak, 2018)
Referring to the Malaysian Timber Standard (MS544: Part 5: 2001), it should be capable in estimating the bolted connection capacity for bearing failure as the development of the code is based on the ductile failure mode. However, in the previous research studies conducted by the author on bolted joints of local hardwoods such as Meraka, Belian and Selangan Batu, it was found that the code provides too conservative design strength values. This can lead to an uneconomical wall-diaphragm connection retrofit design for the unreinforced masonry buildings because of more fabrication of steel in the design output is produced due to the increment of the number or size of bolts. Thus, this present experimental study was performed in an effort to extend the use of European Yield Model (EYM) in predicting the bolted connections for local Kapur hardwood. From the comparison made between the laboratory data and EYM, the potential of the design equation was verified.